2018
DOI: 10.1080/13549839.2018.1531837
|View full text |Cite
|
Sign up to set email alerts
|

Energy made in Northern Friesland: fair enough?

Abstract: Citizen wind parks in the German district of Northern Friesland are a well-known example of the citizen-funded development of wind power. This paper follows the careful (and successful) collective structuring of wind power in Northern Friesland, along with the State of Schleswig-Holstein's attempt, which was challenged and ultimately overturned, to replicate and generalize participation as a basis for scaling up wind power in the region through planning.In so doing, the paper explores the processes of fair pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…To avoid penalizing lower social-grade customers, participation models can also adopt fairness techniques to offer equal opportunities for energy customers [72]. A previous study observed a link between perceived procedural fairness and the acceptance of energy-related projects [73].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid penalizing lower social-grade customers, participation models can also adopt fairness techniques to offer equal opportunities for energy customers [72]. A previous study observed a link between perceived procedural fairness and the acceptance of energy-related projects [73].…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on this lens of socio-material assemblages, founded in Science & Technology Studies (STS), we extend the assemblage thinking introduced more recently in human geography (e.g. Anderson and McFarlane, 2011; Krauss, 2010; Labussière and Nadaï, 2018a; Le Billon and Sommerville, 2017; Kropp, 2018; Chezel and Nadaï, 2019). Exploring the entanglement of wind (as a commodity) and land (as an asset), the lens of socio-technical assemblages helps us to discern how the valuation of wind has reconfigured the valuation of land, and vice versa.…”
Section: Towards An Assemblage Of Land For Harnessing Windmentioning
confidence: 99%
“…The shape that many SLES take is dependent on the local and institutional contexts where they are located [57], with access to finance and resources a major barrier for their development [61,109]. This causes injustice, as poorer communities without access to land are at a disadvantage [48,60]. More research focused on the organisational strategies used to design and implement SLES in more disadvantaged geographies.…”
Section: Community Innovations and Entrepreneurshipmentioning
confidence: 99%